Front Cover: One‐Dimensional Looped Chain and Two‐Dimensional Square Grid Coordination Polymers: Encapsulation of Bis(1, 2, 4‐Triazole)‐trans‐cyclohexane into the Voids (Eur. J. Inorg. Chem. 5/2019). Issue 5 (29th January 2019) - Adarsh, Nayarassery N.; Dîrtu, Marinela M.; Guionneau, Philippe; Devlin, Eamonn; Sanakis, Yiannis; Howard, Judith A. K.; Chattopadhyay, Basab; Garcia, Yann
Abstract : The Front Cover shows the structure of an unprecedented Cu II coordination polymer, which resembles a two‐dimensional square grid architecture. This compound acts as an excellent host for a pharmaceutically important bis(triazole) ligand, namely bis(1, 2, 4‐triazole)‐ trans ‐cyclohexane. The self‐assembly of this type of coordination polymers is affected by various kinetic and thermodynamic factors. More information can be found in theFull Paper by Y. Garcia et al. For more on the story behind the cover research, see theCover Profile .